Sleep staging method based on multi-view fusion and improved dense connection network - WU PENGCHENG; CHEN BAOHONG; FEI KELING; WANG JIANGHUI (2025)
The invention relates to a sleep staging method based on multi-view fusion and an improved dense connection network. The sleep staging method comprises the following steps: acquiring single-channel sleep EEG data as an initial data set; preprocessing the initial data set to form a three-channel two-dimensional time-frequency spectrogram as a target data set; constructing an improved dense connection network as a sleep staging network model by taking the dense connection network as a reference; and sending the target data set into the constructed network model to complete sleep staging discrimination. In order to solve the problems that sleep electroencephalogram frequency components are complex, weak dynamic information is difficult to capture and individual differences of subjects are large, a two-dimensional time-frequency spectrogram generated by single-channel EEG signals serves as a main feature information channel, corresponding spectrograms are generated with the help of FNS and LNDP methods, and local